Noonan syndrome‐associated biallelic LZTR1 mutations cause cardiac hypertrophy and vascular malformations in zebrafish. Issue 3 (28th December 2019) - Nakagama, Yu; Takeda, Norihiko; Ogawa, Seishi; Takeda, Hiroyuki; Furutani, Yoshiyuki; Nakanishi, Toshio; Sato, Tatsuyuki; Hirata, Yoichiro; Oka, Akira; Inuzuka, Ryo
Abstract: Background: Variants in the LZTR1 ( leucine‐zipper‐like transcription regulator 1 ) gene (OMIM #600574) have been reported in recessive Noonan syndrome patients. In vivo evidence from animal models to support its causative role is lacking. Methods: By CRISPR‐Cas9 genome editing, we generated lztr1 ‐mutated zebrafish ( Danio rerio ). Analyses of histopathology and downstream signaling were performed to investigate the pathogenesis of cardiac and extracardiac abnormalities in Noonan syndrome. Results: A frameshift deletion allele was created in the zebrafish lztr1 . Crosses of heterozygotes obtained homozygous lztr1 null mutants that modeled LZTR1 loss‐of‐function. Histological analyses of the model revealed ventricular hypertrophy, the deleterious signature of Noonan syndrome‐associated cardiomyopathy. Further, assessment for extracardiac abnormalities documented multiple vascular malformations, resembling human vascular pathology caused by RAS/MAPK activation. Due to spatiotemporal regulation of LZTR1, its downstream function was not fully elucidated from western blots of adult tissue. Conclusion: Our novel zebrafish model phenocopied human recessive Noonan syndrome and supported the loss‐of‐function mechanism of disease‐causing LZTR1 variants. The discovery of vascular malformations in mutants calls for the clinical follow‐up of patients to monitor for its emergence. The model will serve as a novel platform for investigating the pathophysiology linking RAS/MAPK signaling to cardiac and vascular pathology. Abstract : LZTR1 ( leucine‐zipper‐like transcription regulator 1 ) variants have recently been reported in association with autosomal‐recessive Noonan syndrome, while in vivo evidence from animal modeling experiments is still lacking to support causality. By way of CRISPR‐Cas9 genome editing in zebrafish, we successfully modeled the ventricular hypertrophy seen in Noonan syndrome‐associated cardiomyopathies. Our novel zebrafish model will serve as a novel platform for investigating the pathophysiology linking RAS/MAPK signaling to cardiac and vascular pathology.